2021
DOI: 10.1172/jci.insight.140443
|View full text |Cite
|
Sign up to set email alerts
|

Versatile workflow for cell type–resolved transcriptional and epigenetic profiles from cryopreserved human lung

Abstract: Complexity of lung microenvironment and changes in cellular composition during disease make it exceptionally hard to understand molecular mechanisms driving development of chronic lung diseases. Although recent advances in cell type–resolved approaches hold great promise for studying complex diseases, their implementation relies on local access to fresh tissue, as traditional tissue storage methods do not allow viable cell isolation. To overcome these hurdles, we developed a versatile workflow that allows stor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…1B ). We have previously shown that this step is crucial to ensure exclusion of low-quality control samples presenting additional lung pathologies, which may result in confounding effects in sequencing-based analyse (Llamazares-Prada et al 2021).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…1B ). We have previously shown that this step is crucial to ensure exclusion of low-quality control samples presenting additional lung pathologies, which may result in confounding effects in sequencing-based analyse (Llamazares-Prada et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Lung tissue was cryopreserved upon reception as described previously (Llamazares-Prada et al 2021). Briefly, specimens were transported in CO 2 -idepenent medium (Thermo Fisher Scientific) supplemented with 1% BSA (Carl Roth), 1% penicillin & streptomycin (Fisher Scientific) and 1% Amphotericin B (Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Classical droplet-based scRNA-seq technologies such as Drop-seq, In-Drop, Chromium (10× Genomics, Pleasanton, CA, USA) and Nadia (Dolomite Bio, Royston, UK) are widely used due to their high throughput and reasonable pricing. Although recent approaches in bulk RNA and scRNA-seq applications of cryopreserved cells showed promising results for lung epithelial cells, using viable cells from fresh tissue remains the recommended option by the manufacturers (10× Genomics, Dolomite Bio) of commercially available droplet-based scRNA-seq workflows [ 26 , 27 ]. In plate-based scRNA-seq technologies such as SMART-seq2, single cells are conventionally sorted by flow cytometry into wells in order to overcome the viability shortcoming, as dead cells can be removed during sorting.…”
Section: Basic Principles Of Pulmonary Single-cell Isolation Barcodin...mentioning
confidence: 99%